2015
DOI: 10.1136/bjsports-2014-094388
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Tai Chi on four chronic conditions—cancer, osteoarthritis, heart failure and chronic obstructive pulmonary disease: a systematic review and meta-analyses

Abstract: BackgroundMany middle-aged and older persons have more than one chronic condition. Thus, it is important to synthesise the effectiveness of interventions across several comorbidities. The aim of this systematic review was to summarise current evidence regarding the effectiveness of Tai Chi in individuals with four common chronic conditions—cancer, osteoarthritis (OA), heart failure (HF) and chronic obstructive pulmonary disease (COPD).Methods4 databases (MEDLINE, EMBASE, CINAHL and SPORTDiscus) were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 64 publications
9
69
1
1
Order By: Relevance
“…Tai Chi is a multi‐component, lower‐intensity Chinese mind‐body exercise that consists of slow, flowing movements and incorporates muscle strengthening, balance, postural training, meditation, and deep breath training. Accumulating evidence supports the role of Tai Chi as an effective therapeutic exercise option for patients with chronic pain and other chronic conditions such as fibromyalgia, cancer, heart failure, and chronic obstructive pulmonary disease [33‐35]. In this study, each Tai Chi class lasted 60 minutes and occurred twice weekly over 12 weeks.…”
Section: Methodsmentioning
confidence: 79%
“…Tai Chi is a multi‐component, lower‐intensity Chinese mind‐body exercise that consists of slow, flowing movements and incorporates muscle strengthening, balance, postural training, meditation, and deep breath training. Accumulating evidence supports the role of Tai Chi as an effective therapeutic exercise option for patients with chronic pain and other chronic conditions such as fibromyalgia, cancer, heart failure, and chronic obstructive pulmonary disease [33‐35]. In this study, each Tai Chi class lasted 60 minutes and occurred twice weekly over 12 weeks.…”
Section: Methodsmentioning
confidence: 79%
“…Accumulating evidence supports Tai Chi as an effective therapeutic exercise option for patients with chronic disease 27,28 . In this study, each Tai Chi class lasted 60 minutes and occurred twice weekly over 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic reviews have concluded that there is convincing evidence for the positive effects of Tai Chi on fall prevention (Huang, Feng, Li, & Lv, 2017), depressive symptoms (Chi, Jordan-Marsh, Guo, Xie, & Bai, 2013) and cognitive performance (Wayne et al, 2014) among older people. Tendencies to improve physical performance by Tai Chi exercise was found in chronic conditions such as heart failure and chronic obstructive pulmonary disease (Chen, Hunt, Campbell, Peill, & Reid, 2015). Tai Chi has even been found to be a safe form of physical exercise for patients with CHF, without reported side effects (Barrow, Bedford, Ives, O′Toole, & Channer, 2007;Yeh et al, 2004).…”
mentioning
confidence: 99%